The scent of murder - Logan, Kylie (Logan, Kylie. Jazz Ramsey., 2019)
First in a new series from national bestselling author Kylie Logan, The Scent of Murder is a riveting mystery following Jazz Ramsey as she trains cadaver dogs. The way Jazz Ramsey figures it, life is pretty good. She's thirty-five years old and owns her own home in one of Cleveland's most diverse, artsy, and interesting neighborhoods. She has a job she likes as an administrative assistant at an all-girls school, and a volunteer interest she's passionate about--Jazz is a cadaver dog handler. Jazz is working with Luther, a cadaver dog in training. Luther is still learning cadaver work, so Jazz is putting him through his paces at an abandoned building that will soon be turned into pricey condos. When Luther signals a find, Jazz is stunned to see the body of a young woman who is dressed in black and wearing the kind of make-up and jewelry that Jazz used to see on the Goth kids back in high school. She's even more shocked when she realizes that beneath the tattoos and the piercings and all that pale make up is a familiar face. The lead detective on the case is an old lover, and the murdered woman is an old student. Jazz finds herself sucked into the case, obsessed with learning the truth.